Confocal laser scanning microscopy and ultrastructural study of VGLUT2 thalamic input to striatal projection neurons in rats. Issue 6 (20th February 2013) - Lei, Wanlong; Deng, Yunping; Liu, Bingbing; Mu, Shuhua; Guley, Natalie M.; Wong, Ting; Reiner, Anton
Abstract We examined thalamic input to striatum in rats using immunolabeling for the vesicular glutamate transporter (VGLUT2). Double immunofluorescence viewed with confocal laser scanning microscopy (CLSM) revealed that VGLUT2+ terminals are distinct from VGLUT1+ terminals. CLSM of Phaseolus vulgaris‐leucoagglutinin (PHAL)‐labeled cortical or thalamic terminals revealed that VGLUT2 is rare in corticostriatal terminals but nearly always present in thalamostriatal terminals. Electron microscopy revealed that VGLUT2+ terminals made up 39.4% of excitatory terminals in striatum (with VGLUT1+ corticostriatal terminals constituting the rest), and 66.8% of VGLUT2+ terminals synapsed on spines and the remainder on dendrites. VGLUT2+ axospinous terminals had a mean diameter of 0.624 μm, while VGLUT2+ axodendritic terminals a mean diameter of 0.698 μm. In tissue in which we simultaneously immunolabeled thalamostriatal terminals for VGLUT2 and striatal neurons for D1 (with about half of spines immunolabeled for D1), 54.6% of VGLUT2+ terminals targeted D1+ spines (i.e., direct pathway striatal neurons), and 37.3% of D1+ spines received VGLUT2+ synaptic contacts. By contrast, 45.4% of VGLUT2+ terminals targeted D1‐negative spines (i.e., indirect pathway striatal neurons), and only 25.8% of D1‐negative spines received VGLUT2+ synaptic contacts. Similarly, among VGLUT2+ axodendritic synaptic terminals, 59.1% contacted D1+ dendrites, and 40.9% contacted D1‐negative dendrites. VGLUT2+ terminals on D1+ spines and dendrites tended to be slightly smaller than those on D1‐negative spines and dendrites. Thus, thalamostriatal terminals contact both direct and indirect pathway striatal neurons, with a slight preference for direct. These results are consistent with physiological studies indicating slightly different effects of thalamic input on the two types of striatal projection neurons. J. Comp. Neurol., 521:1354–1377, 2013. © 2012 Wiley Periodicals, Inc.